Democratic Republic of Sao Tome and Principe : Poverty Reduction Strategy Paper; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents an update to the Poverty Reduction Strategy Paper (PRSP) for the Democratic Republic of Sao Tome and Principe. It discusses that a tendency toward continual growth of the unemployment levels was verified in the urban region between 2000 and 2003 while during the same period, a tendency of continual decrease in the rural zone was detected, with a few variations. The variation rate of unemployment in the urban zone during the period between 2000 and 2003 was 48 percent while the variation rate of unemployment in the rural region was 16.5 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet